The Response of Physical, Cognitive, Emotional in Patients with Mental Disorders Who Performed The Action Restraint - Yuniar Dewi; Sawab Sawab; Ramelan Sugijana (Poltekkes Kemenkes Semarang, 2019)
Background: Handling is often done in mental hospitals is binding or restraint. Restraint is the act of someone using a rope bridle are made to control aggressive behavior arising from maladaptive response in the patient, control patients with severe mental disorders, prevent injuries, and reduce agitation and aggressive behavior.Purpose: The study aims to describe the response of physical, cognitive, emotional in patients with mental disorders who performed the action restraint in UPIP Prof.Dr.Soerojo Magelang.Methods: The study design was used descriptive explorative. Samples taken by total sampling as many as 51 patients. Research tool using a questionnaire responses of physical, cognitive, emotional in patients with mental disorders who do act restraint Data was analyzed by univariate. emotions on mental patients who do act restraint consisting of 6 physical response questions, 8 questions cognitive responses, and 7 questions emotional response.Results: The results of this study with the respondent amounted to 51 patients showed early adult aged respondents were 19 patients (37.3%), male sex were 51 patients (100%), the majority of elementary education by 25 patients (49%). Physical responses in patients with mental disorders who do restraint that is included in the heavy physical response by 36 patients (70.6%), cognitive responses indicate cognitive responses were 28 patients (54.9%), emotional responses indicate emotional responses were as many as 23 patients (45.1%).Conclusion: Patients with mental disorders are at high risk for behaving amuck which is a form of aggressive behavior, patient amok need more specialized treatment.